Strengthening global competence through sister school programs - Arista Khusnul Fadila; Yayuk Hidayah; Meiwatizal Trihastuti (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2026)
Civic education is fundamentally mandated to cultivate the requisite skills, character, and knowledge necessary to forge exemplary citizens. Amidst the relentless progression of globalisation, it is an absolute imperative for educators to construct pedagogical strategies strictly aligned with 21st-century demands. Globalisation unequivocally dictates that citizens possess a robust global perspective; therefore, foundational education must definitively foster global citizenship from an early age. Schools serve as indispensable institutions in expanding the cognitive frameworks and international roles of young citizens. Consequently, this study purposefully examines the implementation of the sister school programme as a critical mechanism for developing students' global perspectives. Employing a qualitative Systematic Literature Review methodology, this research rigorously analyses existing empirical evidence. The findings conclusively demonstrate that the sister school programme provides essential platforms for direct, transnational student interaction, thereby playing a paramount role in augmenting global perspectives. Through collaborative pedagogical activities, cross-border communication, and cultural exchange, students systematically broaden their comprehension of cultural diversity. This proactive engagement forcefully cultivates the tolerance and intellectual openness indispensable in the modern era, while definitively fortifying practical competencies in foreign language acquisition and digital communication.